Efficacy and Effect of Inhaled Adenosine Treatment in Hospitalized COVID-19 Patients - Caracciolo, Massimo; Correale, Pierpaolo; Mangano, Carmelo; Foti, Giuseppe; Falcone, Carmela; Macheda, Sebastiano; Cuzzola, Maria; Conte, Marco; Falzea, Antonella Consuelo; Iuliano, Eleonora; Morabito, Antonella; Caraglia, Michele; et al. (Frontiers in Immunology, 2021)
Lack of specific antiviral treatment and a preventative vaccine for COVID-19 has resulted in long hospitalizations and high mortality rate. By harnessing the regulatory effects of adenosine on inflammatory mediators, we have instituted a new therapeutic treatment with inhaled adenosine in COVID-19 patients, with the aim of reducing inflammation, the onset of cytokine storm, and therefore to improve prognosis. The use of inhaled adenosine in COVID19 patients has allowed reduction of length of stay, on average 6 days. This result is strengthened by the decrease in SARS-CoV-2 positive days. In treated patients compared to control, a clear improvement in PaO2/FiO2 was observed together with a reduction in inflammation parameters, such as the decrease of CRP level. Furthermore, the efficacy of inhaled exogenous adenosine led to an improvement of the prognosis indices, NLR and PLR. The treatment seems to be safe and modulates the immune system, allowing an effective response against the viral infection progression, reducing length of stay and inflammation parameters.